Through the Looking Glass of Digital Storytelling in Adult Education - Cathy Mullett; Ruby Cain (Adult Education Research Conference, 2014)
Incorporating digital storytelling into online course environment can aid in the development of a productive and engaging community of learning. Adult learning strategies addressed are: Use of stories to illustrate content and highlight key points; “Storying” the curriculum; and making autobiographical connections with the content.